Narratives about Being and Becoming English Language Teachers in an ELT Education Program - Castañeda Trujillo, Jairo Enrique; Alarcón Camacho, Eliana Maritza; Jaime Osorio, María Fernanda (Colombian Applied Linguistics Journal, 2022)
This article presents an analysis of the narratives written by four pre-service English language teachers (PELTs) during the last semester of their undergraduate program. The study aims to understand the constructions related to being and becoming PELTs and the possible contributions that the English language teacher (ELT) education program provided to shape those identities. The narratives were reconstructed from two narrative frames written by the PELTs and their responses to a narrative interview. The results reveal how participants (re)signify their profession from their experiences in the program, the teaching practicum, and other settings. PELTs construct and consolidate their professional identity initially from a technical perspective. However, their experiences and the guidance of some teacher educators transformed their view of education into a more critical and informed perspective. In conclusion, professional identity could potentially be formed and changed based on the experiences provided throughout the PELTs’ education. Considering this, initial English teacher education programs should establish strategies that contribute to this end from the beginning of undergraduate studies.